2017
DOI: 10.34204/jiafe.v3i2.767
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Transparansi Dan Komitmen Terhadap Akuntabilitas Pengelolaan Anggaran

Abstract: This study aims to examine and analyze the effect of transparency and commitment to the budget management in Bekasi City simultaneously and partial in period 2014. This study uses the population, namely the budget administrator and representatives of school committees Bekasi City where in 2014 the number of high school by 70. Meanwhile, samples took as many as 210 respondents by cluster sampling method and used primary data by distributing questionnaires. From this study we concluded that transparency and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
4
7
0
2
Order By: Relevance
“…It is in line with the stewardship theory, which shows that philosophically human nature is trustworthy and has integrity and honesty towards other parties. This study also supports research by Hendratmi (2017), which states that transparency has a positive effect on budget management and Putra's research (2019); Herawati (2017) also states that transparency has a positive effect on budget management.…”
Section: Transparency Has a Positive Effect On Budget Managementsupporting
confidence: 88%
“…It is in line with the stewardship theory, which shows that philosophically human nature is trustworthy and has integrity and honesty towards other parties. This study also supports research by Hendratmi (2017), which states that transparency has a positive effect on budget management and Putra's research (2019); Herawati (2017) also states that transparency has a positive effect on budget management.…”
Section: Transparency Has a Positive Effect On Budget Managementsupporting
confidence: 88%
“…Accountability, in this context, is defined as taking responsibility for public fund management (Hendratmi, 2017). One form of local government accountability involves using a financial reporting mechanism to create financial statements.…”
Section: Weaknesses Of the Internal Control System And Local Governme...mentioning
confidence: 99%
“…The results of Ema, T.C, (2017), Wahida (2015) research showed that the presentation of accountability reports has a significant positive influence on the transparency of regional financial management. Hendratmi, et. al, (2017) shows that the presentation of accountability reports has a positive influence on the transparency of regional financial management.…”
Section: The Effect Of Presenting Accountability Report On Transparencymentioning
confidence: 99%
“…Kurniawan & Rahayu (2018) suggest that accessibility has a significant influence on the accountability of regional financial statements. Hendratmi (2017) showed that transparency has a positive and significant effect on the accountability of village fund allocation management.…”
Section: Introductionmentioning
confidence: 99%